Café da manhã, edição com Eugénio Costa Almeida e Mário Pinto de Andrade - Almeida, E. C. (Rádio LAC, 2023)
Debate with Professor Mário Pinto de Andrade, on the Angolan radio station Rádio Luanda Antena Comercial (LAC), on the program "Café da Manhã" where, for around 1 hour and 39 minutes, we analyzed and debated the recent Coups d'Etat in Africa and the impact on the Continent. _______________ Debate com o Professor Mário Pinto de Andrade, na rádio angolana Rádio Luanda Antena Comercial (LAC), no programa "Café da Manhã» onde, durante cerca de 1 hora e 39 minutos, analisámos e debatemos os recentes Golpes de Estado em África e o impacto no Continente